Penerapan Masrahiyyah dalam Pembelajaran Maharah al-Kalam di IKHAC Mojokerto - Nahdliyyatul Azimah (An-Nuqthah, 2022)
Learning kalām is not enough just with a monologue model or paired dialogue in class. For some students whose background is lacking in linguistic and psychological aspects, creativity and synergy in the practice of kalām are needed. One of the learning strategies that can accommodate these needs is maṣrāḥiyyah. This study aimed to describe the application of maṣrāḥiyyah for kalām proficiency for students Arabic Language Education Departement of IKHAC Mojokerto batch 2021. The researcher used a descriptive-qualitative approach. There was a change in the willingness and ability of students in the didactic aspect and mentality. Maṣrāḥiyyah activities are important to stimulate kalām skills in the frame of sharing roles and can be immortalized through a digital platform to become a reference model for learning kalām skills.